Rumor de clásicos: el grito de algunos autores «invisibles» del teatro español del siglo XX - López Fonseca, Antonio (Cuadernos de Filología Clásica. Estudios Latinos, 2006)
This paper intends to introduce the reader to the work of some Spanish XXth century playwrights, off the commercial stage, that recurred to classical myths in order to face after war Spanish reality. Such playwrights as A. Martínez Ballesteros, R. Gil Novales, J. G. Schroeder and J. Gállego chose to represent Spanish every day life and reality through the essentially timeless myths of Orestes and Phaedra.
Keywords: Classical Tradition; Spanish XXth century Theatre; Orestes; Phaedra